Parallels, prescience and the past: analogical reasoning and contemporary international politics - Mumford, Andrew (Springer, 2015)
Analogical reasoning has held a perpetual appeal to policymakers who have often drafted in historical metaphor as a mode of informing decision-making. However, this article contends that since the beginning of the ‘War on Terror’ we have arguably seen the rise of a more potent form of analogy, namely ones that are selected because they fulfil an ideological function. Analogical reasoning as a tool of rational decision-making has increasingly become replaced by analogical reasoning as a tool of trenchant ideologically-informed policy justification. This article addresses three key areas which map out the importance of analogical reasoning to an understanding of developments in contemporary international politics: the relationship between history and politics, in intellectual and policy terms; a critical assessment of the appeal that analogical reasoning holds for policymakers; and the development of a rationale for a more effective use of history in international public policymaking.